PENERAPAN RELAKSASI NAFAS DALAM TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI WILAYAH KERJA RAWAT INAP RSUD KARAWANG - Rina Fera; Wirdan Fauzi Rahman (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Hypertension is often referred to as the silent killer, because often sufferers go for years without feeling any disturbances or symptoms. Without realizing it, patients experience complications with vital organs such as the heart, brain or kidneys. One of the non-pharmacological therapies that must be carried out by hypertension sufferers is relaxation. Deep breathing relaxation is one type of relaxation that can be done in patients with hypertension. The design of this scientific paper uses a case study design. The subjects used were two patients with hypertension. Data analysis was carried out using descriptive analysis. The results of the application showed that after applying deep breathing relaxation for 3 days, there was a decrease in blood pressure in patients with hypertension in subject I (Mrs. S) from 175/100 mmHg to 130/90 mmHg and in subject II (Mrs. M) from 170 mmHg. /100 mmHg to 140/98 mmHg. Conclusion This deep breathing relaxation action is effective for lowering blood pressure in hypertensive patients. Suggestions for hypertensive patients should be able to apply deep breathing relaxation independently to help lower or control blood pressure.